Three minimum guidelines for argumentative control in administrative and legislative headquarters on public policies - Montoya-Camarena, Ramsés Samael; Avendaño-González, Luis Eusebio Alberto (DIXI, 2023)
Introduction: The objective of the text is to offer three minimum guidelines for argumentative control in the elaboration of public policies by the administrative and legislative spheres, for this purpose, the work deals with two aspects. The first raises the importance of the binomial deliberative democracy and constitutional rule of law, for the legislative function. The second justifies the importance of having evaluation guidelines for the control of legislative argumentation and offers a trigonometric model to analyze public policies. Methodology: In the present work, based on documentary research, the problem of the investigation is approached from legal realism, particularizing the study to specific cases with their respective explanation. In addition to the comparative method in the confrontation of applicable legislation. Results: The deliberative turn in democratic theory is strongly linked to modern constitutionalism, whose engine of legitimacy is the protection of fundamental rights. Conclusions: It is concluded that the deliberative space is a vigilant and permanent interaction between the tensions and frictions of the demands of the community that seek the common point of relief of claims and protection of rights.